Comparison of prognosis between coronary computed tomography angiography versus invasive coronary angiography for stable coronary artery disease: a systematic review and meta-analysis - Xie, Qingya; Zhou, Lingling; Li, Ying; Zhang, Ruizhe; Wei, Han; Ma, Gaoxiang; Tang, Yuping; Xiao, Pingxi (Frontiers in Cardiovascular Medicine, 2023)
Background: The impact of using invasive coronary angiography (ICA) or coronary computed tomography (CCTA) as an initial examination on the incidence of major adverse cardiovascular events (MACEs) in patients with stable coronary artery disease and the occurrence of major operation-related complications is uncertain. Objective: This study aimed to explore the effects of ICA versus CCTA on MACEs, all-cause death, and major operation-related complications. Methods: A systematic search of electronic databases (PubMed and Embase) was conducted for randomized controlled trials and observational studies comparing MACEs between ICA and CCTA from January 2012 to May 2022. The primary outcome measure was analyzed using a random-effects model as a pooled odds ratio (OR). The main observations were MACEs, all-cause death, and major operation-related complications. Results: A total of six studies, comprising 26,548 patients, met the inclusion criteria (ICA n = 8,472; CCTA n = 18,076). There were statistically significant differences between ICA and CCTA for MACE (OR 1.37; 95% confidence interval [CI], 1.06-1.77; p = 0.02), all-cause death (OR 1.56; 95% CI, 1.38-1.78; p < 0.00001), and major operation-related complications (OR 2.10; 95% CI, 1.23-3.61; p = 0.007) among patients with stable coronary artery disease. Subgroup analysis demonstrated statistically significant results in the impact of ICA or CCTA on MACEs according to the length of follow-up. Compared to CCTA, ICA was related to a higher incidence of MACEs in the subgroup with a short follow-up (≤3 years) (OR 1.74; 95% CI, 1.54-1.96; p < 0.00001). Conclusions: Among patients with stable coronary artery disease, an initial examination with ICA was significantly associated with the risk of MACEs, all-cause death, and major procedure-related complications compared to CCTA in this meta-analysis.